Proposed upgrading of D’Yan chalet for Majlis Daerah Yan at Peranginan Titi Hayun, Yan Kedah Darul Aman / Nur Lily Suraya Rijali - Rijali, Nur Lily Suraya (Faculty of Architecture, Planning and Surveying, 2011)
Project report is an important thing for students Diploma in Interior Architecture. This is because in order to gauge students understanding of research insolving the problems of a project. Project selected for the final project is Proposed Upgrading of D’Yan chalet for Majlis Daerah Yan at Peranginan Titi Hayun, Yan Kedah Darul Aman. D’Yan chalet built by the Majlis Daerah as an accomodation to visitors who want to experience the natural environment. D’Yan chalet is also a guesthouse in the village owned by the Majlis Daerah Yan. Visitor here in the village owned by the Majlis Daerah Yan. Visitor herein the village owned by the Majlis Daerah Yan. Visitor here will enjoy the local fruits for free. Located 3 miles from town Yan and its location in the area Peranginan Titi Hayun and Tangga Kenari 1000 years of natural waterfalls and flora and fauna.